Determinants of intention to utilise green technology financing scheme (GTFS), the moderating effect of perceived risk, and the influence of intention to utilise towards utilisation behaviour: an application of UTAUT2 model in the nontechnology context / Abd Hadi Mustaffa - Mustaffa, Abd Hadi (2022)
The Malaysian government has provided green financing initiatives to encourage companies to embark on those projects, known as Green Technology Financing Scheme (GTFS). It has been offered since 2010, and RM 3.5 billion allocated funds have been utilised within seven years. However, despite the huge amount of allocated funds, the utilisation has been relatively slow and underutilised. The main issue highlighted was related to the Green Industry Players (GIPs) side for four reasons. The first reason is difficulties in a late payment to the project's progress due to poor cash flow management. The second reason is GIPs face performance risks of GTFS such as credit default, failing to deliver the success of green projects, or not receiving government guarantees. The third reason is that GIPs face the effort risk of GTFS such as difficulties in applying financing schemes due to the inability to fulfil requirements and guidelines. The fourth and final reason is related to the eight determinants influencing GIPs intention to utilise GTFS. For those reasons, it concludes that GTFS is considered high risk with little or no success story in the past. Hence, there are four objectives of this study. The first is to examine the determinants of intention to utilise GTFS among GIPs in Malaysia. The second is to determine if perceived risk delivers moderating effect on the relationship between performance expectancy and intention to utilise GTFS among GIPs in Malaysia. The third is to determine if perceived risk delivers moderating effect on the relationship between effort expectancy and intention to utilise GTFS among GIPs in Malaysia. Fourth, to examine the GIPs influence on intention to utilise towards utilisation behaviour of GTFS in Malaysia. The data is collected from 175 certified Green Industry Players (GIPs) who have experience applying and utilising the Green Financing Scheme in Malaysia. Partial Least Square-Structural Equation Model (PLSSEM) is used to analyse all results and findings. There are four key findings in this study. The first objective revealed that performance expectancy, facilitating conditions, price value and trust significantly influence the intention to utilise GTFS among GIPs in Malaysia. However, effort expectancy, social influence, hedonic motivation and habit do not significantly influence the intention to utilise GTFS among GIPs in Malaysia. The second objective revealed that perceived risk significantly weakened (negative) the relationship between performance expectancy and intention to utilise GTFS among GIPs in Malaysia. The third objective discovered that perceived risk significantly strengthened (positive) the relationship between effort expectancy and intention to utilise GTFS among GIPs in Malaysia. The fourth and final objective discovered that the intention to utilise significantly influences the utilisation behaviour of GTFS among GIPs in Malaysia. There are four contributions highlighted. First, this study will benefit GIPs in identifying the determinants influencing the intention to utilise GTFS. Second, trust can potentially become an additional construct in UTAUT2 theory in the future. Third, perceived risk can be considered and potentially become a new moderating variable in the UTAUT2 theory in the future. Fourth, the medium explanatory and predictive power result indicates that UTAUT2 also be applied in the non-technology context. Fifth and final, this study will benefit the government as policymakers to improve future green financing schemes regarding policy, features, and packages.